SECKEL SYNDROME IN A - 2 YEAR OLD GIRL - Yulius Malino, Imanuel; Arimbawa, Made; Suryawan, Bikin (Medicina, 2013)
Seckel syndrome is a frequent autosomal recessive that cause microcephalic osteodysplastic dwarfisms. It characterized with proportionate dwarfism of prenatal onset , dysmorphic features including severe microcephaly and “ bird-headed ” like appearance, mental retardation and autosomal recessive inheritance , because defect on chromosome 3q22.1-q24 (SCKL1), chromosome 18p11.31-q11.2 (SCKL2) and chromosome 14q23 (SCKL3). We report ed , 2 years, 8 months female with intrauterine growth re striction , severe proportionately short stature, a “bird-headed” profile with receding forehead, large eyes, breaks like protrusion of the nose, narrow face, receding lower jaw and micrognathia and from bone survey we found a retarded bone age on which was appropriate for 6 months of age. There was no other systems dissorder have been found and no specific medication has been given. Patient was hospitalized to establish diagnosis and was discharge dafter ten days of hospitalization Normal 0 false false false IN X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Seckel syndrome, SCKL 1, SCKL 2, SCKL 3, “bird-headed” profile